Forensic radiology: An emerging tool in identification - Raghav Kumar; Appaji Athota; Trisha Rastogi; Sunil Kumar Karumuri (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
In any mass disaster condition, identification of the person is most important. For this purpose, the forensic investigators use different methods for identifying the dead. They consider skeletal remains of the dead as the initial step in identification. Radiographs carry great evidence to act as antemortem records and also assist in identifying the person, age, gender, race, etc. Forensic dentistry is also emerging as a new branch in forensics. So, the forensic dentist must be aware of different techniques, developments, and resources to incorporate the technology in order to achieve success in human identification. So, our aim of the present review is to focus on different radiological techniques and new developments available for successful identification of the dead.